4
$\begingroup$

How to prove

$$\zeta(2)-\log(x)\log(1-x)=\operatorname{Li}_2(x)+\operatorname{Li}_2(1-x)$$ I havent started, any hints?

$\endgroup$
  • $\begingroup$ Note: this is called the dilog reflection formula. The duplication formula is something else. $\endgroup$ – David H Dec 7 '14 at 18:31
8
$\begingroup$

$\newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\dsc}[1]{\displaystyle{\color{red}{#1}}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\Li}[1]{\,{\rm Li}_{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}$ \begin{align}&\color{#66f}{\large\Li{2}\pars{x} + \Li{2}\pars{1 - x}} \\[5mm] & = -\int_{0}^{x}{\ln\pars{1 - t} \over t}\,\dd t\ -\ \overbrace{\int_{0}^{1 - x}{\ln\pars{1 - t} \over t}\,\dd t} ^{\dsc{t\ \mapsto 1 - t}} \\[5mm]&=-\int_{0}^{x}{\ln\pars{1 - t} \over t}\,\dd t +\int_{1}^{x}{\ln\pars{t} \over 1 - t}\,\dd t \\[8mm]&=-\int_{0}^{x}{\ln\pars{1 - t} \over t}\,\dd t -\left.\vphantom{\Large A}\ln\pars{1 - t}\ln\pars{t} \right\vert_{\, t\ \to\ 1^{-}}^{\, t\ =\ x} \\[2mm] & +\int_{1}^{x}\ln\pars{1 - t}\,{1 \over t}\,\dd t \\[8mm]&=-\ln\pars{1 - x}\ln\pars{x} -\int_{0}^{1}{\ln\pars{1 - t} \over t}\,\dd t \\[5mm] & = -\ln\pars{1 - x}\ln\pars{x} + \int_{0}^{1}\Li{2}'\pars{t}\,\dd t \\[5mm]&=-\ln\pars{1 - x}\ln\pars{x} +\ \overbrace{\Li{2}\pars{1}}^{\dsc{\zeta\pars{2}}}\ =\ \color{#66f}{\large\zeta\pars{2} - \ln\pars{x}\ln\pars{1 - x}} \end{align}

$\endgroup$
9
$\begingroup$

Consider: $$ f(x)=\log(x)\log(1-x)+\operatorname{Li}_2(x)+\operatorname{Li}_2(1-x).$$ We want to show that $f$ is constant, hence we compute $f'$: $$ f'(x) =\left(\frac{\log(1-x)}{x}-\frac{\log(x)}{1-x}\right)-\frac{\log(1-x)}{x}+\frac{\log x}{1-x}=0. $$ To finish the proof, we just need to compute $f(x)$ in a point, or to compute the limit: $$ \lim_{x\to 1^-} f(x) = \zeta(2)+\lim_{x\to 1^-}\log(x)\log(1-x)=\zeta(2).$$

Notice that we have a nice corollary: $$\sum_{n\geq 1}\frac{1}{2^n n^2}=\operatorname{Li}_2\left(\frac{1}{2}\right)=\frac{1}{2}\left(f\left(\frac{1}{2}\right)-\log^2 2\right)=\frac{\pi^2}{12}-\frac{\log^2 2}{2}.$$

$\endgroup$
  • 3
    $\begingroup$ Excellent, simple, and very useful. $\endgroup$ – Ron Gordon Dec 7 '14 at 18:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.